Effectiveness Of Village Funds For Economic Development And Infrastructure Of Bonto Jai Village, Bissappu District In Bantaeng Regency - Ihdina Dewi Dewi (Pustaka Digital Indonesia, 2021)
The purpose of this study was to determine the effectiveness of village funds for economic and infrastructure development in Bonto Jai Village, Bissappu District, Bantaeng Regency. This type of research is qualitative research. The processed data is the result of interviews conducted with 6 informants namely the Village Head, Village Secretary, Planning and General Affairs Head, Hamlet Head and the community. Data collection methods used in this study were observation, interviews and documentation. The results of the research obtained are that the Economic and Infrastructure Development Program of Bonto Jai Village, Bissappu District in Bantaeng Regency has been running quite well when viewed from the three effectiveness inductors starting from the first indicator, namely the achievement of objectives, where in the implementation of the program all are implemented and resolved with on time and on target, the second indicator is integration, where the program has been or has been socialized first in village meetings before implementing the development program, then the third indicator is adaptation, where program planning and implementation are carried out in stages and in accordance with the provisions.